1997
DOI: 10.1103/physrevc.55.1074
|View full text |Cite
|
Sign up to set email alerts
|

Photodisintegration of the triton with realistic potentials

Abstract: The process $\gamma + t \to n + d$ is treated by means of three-body integral equations employing in their kernel the W-Matrix representation of the subsystem amplitudes. As compared to the plane wave (Born) approximation the full solution of the integral equations, which takes into account the final state interaction, shows at low energies a 24% enhancement. The calculations are based on the semirealistic Malfliet-Tjon and the realistic Paris and Bonn B potentials. For comparison with earlier calculations we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The results are the two-body breakup cross sections for 3 H [1]. The same shape for the 3 He cross section has been reported but with the lower magnitude.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…The results are the two-body breakup cross sections for 3 H [1]. The same shape for the 3 He cross section has been reported but with the lower magnitude.…”
Section: Introductionsupporting
confidence: 71%
“…In many theoretical treatments, by solving the three-nucleon Faddeev equations based on simple finite rank forces, it is found that the interacting three-nucleon continuum is crucial for understanding the process in threebody reactions [2]. Sandhas and his collaborators investigated many theoretical treatments of photo-effect in 3 H and 3 He three-nucleon systems by employing the realistic nucleon-nucleon forces exclusive process at 0-40 MeV energies [3,4]. For covering a larger energy range, the inclusive two-and three-body breakup cross sections have been studied by Efros et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a clear discrepancy between both groups of potentials. It should be emphasized that this discrepancy did not show up in our previous calculations [10], due to the incomplete treatment of relative partial waves mentioned above. While in these previous calculations all potentials seemed to favor in this energy region the measurements by Skopik et al [28] (this is still true for Yamaguchi and MT), just the realistic ones lie now between these data and the ones by Kosiek et al [26].…”
Section: Potential Dependencementioning
confidence: 57%
“…We, moreover, mention that consistently with the approximation (1.11) the triton wave function may be determined by solving the homogeneous counterpart of equation (1.12). For details we refer to [10][11][12]. Three-body photonuclear integral equations were first derived within the Faddeev framework by Barbour and Phillips [13].…”
Section: Three-body Equationsmentioning
confidence: 99%
See 1 more Smart Citation